2015
DOI: 10.1155/2015/395826
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Consequences of Antiviral Therapy on HIV-1

Abstract: A variety of enzyme inhibitors have been developed in combating HIV-1, however the fast evolutionary rate of this virus commonly leads to the emergence of resistance mutations that finally allows the mutant virus to survive. This review explores the main genetic consequences of HIV-1 molecular evolution during antiviral therapies, including the viral genetic diversity and molecular adaptation. The role of recombination in the generation of drug resistance is also analyzed. Besides the investigation and discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…Again, note that the main catalytic sites of the integrase are aspartic and glutamic acids (Asp-64, Asp-116 and Glu-152) [48,49]. Comparing HIVin and HIVb, or VIRin and WAG, we also observed a few amino acid changes with an increase in their relative rate of change, such as isoleucine/methionine, isoleucine/leucine, leucine/methionine and serine/threonine (in HIVin) or cysteine/tyrosine (in VIRin), where the amino acids involved presented similar physicochemical properties, agreeing with selection pressure for the maintenance of the protein function [40,50,51].…”
Section: Novel Empirical Substitution Models For Hiv and General Virus Protease And Integrasesupporting
confidence: 75%
See 1 more Smart Citation
“…Again, note that the main catalytic sites of the integrase are aspartic and glutamic acids (Asp-64, Asp-116 and Glu-152) [48,49]. Comparing HIVin and HIVb, or VIRin and WAG, we also observed a few amino acid changes with an increase in their relative rate of change, such as isoleucine/methionine, isoleucine/leucine, leucine/methionine and serine/threonine (in HIVin) or cysteine/tyrosine (in VIRin), where the amino acids involved presented similar physicochemical properties, agreeing with selection pressure for the maintenance of the protein function [40,50,51].…”
Section: Novel Empirical Substitution Models For Hiv and General Virus Protease And Integrasesupporting
confidence: 75%
“…Actually, we benefited from the large number of sequences that are available for these proteins. Note that they have been frequently sequenced due to their relevant role as common antiretroviral drug targets [ 39 , 40 , 41 , 42 ]. Next, we found that the large number of sequences present in some method datasets (in particular, those with more than 10,000 sequences, which are 3 of the 4 method datasets) caused computational limitations that forced us to split them into 10 partitions with the same size ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This represented a large increase in ART coverage, from 9.9% in 2003 to 96.6% in 2014, which coincided with a significant decrease in HIV/AIDS patient mortality from 11.6 to 2.6% [16]. However, with the increase in antiretroviral drug use, the frequency of adaptive mutations in HIV-1 has also increased, generating drug-resistant strains [19]. This has created severe clinical and epidemiological problems [20].…”
Section: Introductionmentioning
confidence: 99%
“…DRM is based on rapid viral evolution and high levels of genetic variability in HIV-1 [1,[12][13][14]. Long-term ARV therapy results in drug selective immune pressure on the HIV-1 population, which causes mutations of viral peptides as the virus attempts to escape the host immune system.…”
Section: Discussionmentioning
confidence: 99%